Incorporation of Resonators Into Plenum Window - LEE, Hsiao Mun; HARIS, Andi; LIM, Kian Meng; XIE, Jinlong; LEE, Heow Pueh (Archives of Acoustics, 2018)
A plenum window with incorporation of Helmholtz resonators in between two glass panes was tested in a reverberation room. The effects of jagged flap on reducing strength of diffracted sound was also investigated in the present studies where white, traffic and construction noises were examined during each set of experiment. When the noise source was located at the central line of the plenum window, the plenum window with Helmholtz resonators was able to mitigate 8.5 dBA, 8.9 dBA and 8.2 dBA of white, traffic and construction noises, respectively, compared with the case of without window. These amounts of noises that attenuated by the plenum window were slightly higher than the case where noise source was diverged 30X away from the plenum window. The effects of jagged flaps on the acoustical performance of the plenum window were negligible. The Helmholtz resonators had the best performance in the frequency region between 900 Hz to 1300 Hz where in this frequency range, the plenum window with Helmholtz resonators was able to attenuate additional 1.7 dBA, 1.9 dBA and 1.6 dBA of white, traffic and construction noises, respectively, compared with the case of without resonators.